Antibodies to the Muscarinic Acetylcholine Receptor M3 in Primary Biliary Cholangitis Inhibit Receptor Function on Cholangiocytes - Mayer, Christian; Preuss, Beate; Grottenthaler, Julia; Berg, Christoph; Klein, Reinhild (Frontiers in Immunology, 2020)
Background&Aims: In primary biliary cholangitis (PBC) antibodies to a peptide of the musca-rinic acetylcholine receptor 3 (mAChR3) have been described. Since the m3AChR is ex-pressed on cholangiocytes and mAChR3-signalling is involved in the pathogenesis of chronic inflammatory biliary diseases, we wanted to investigate whether anti-m3AChR-antibodies influence the function of the recep¬tor and the pro¬liferative response of cholangiocytes. Methods: Immunoglobulins were isolated by ammonium sulphate precipitation using sera from patients with PBC (n=63) and with other chronic liver disorders (n=150). All immuno-globulins were analysed by a lumi¬nometric assay using Chinese hamster ovary (CHO) cells overexpressing the mAChR3 and cholangiocytes (TFK-1-cells) expressing the receptor con-stitutively. Proliferation of TFK-1-cells was measured by 3H-thymidine assay. PBC patients were also analysed in the follow up. Results: Antibodies inhibiting the mAChR3 were found in 49% and 79% of PBC pa¬tients using CHO-cells or TFK-1-cells, respectively, but only in up to 26% of controls (p<0.01). Stimulatory antibodies were hardly detected. Antibody reactivity only mar¬ginally changed during the course of the disease independently of the choice of treatment (ursodeoxycholic acid, immunosuppressive therapy, no medication). The antibodies were more frequently found in PBC patients with a be¬nign course (96%) than in patients with active disease progressing to late stages within 10 years (57%; p<0.01). Proliferation of TFK-1-cells was not influenced by immuno¬globulins from PBC-patients. Conclusion: Sera from patients with PBC contain inhibitory antibodies to the mAChR3 with-out influencing TFK-1-cell proliferation. These antibodies were predominantly ob¬served in pa-tients with non-progressing PBC.